From Text to Context: The Social Impact of Contemporary Literary Themes in Multicultural Communities - Prima Dewi Kusumawati; Lucy Lidiawati Santioso; Noorhani Dyani Laksmi (Journal of Humanities Research Sustainability, 2026)
Background. Contemporary literature increasingly functions as a social medium through which multicultural communities negotiate identity, belonging, and coexistence. In plural societies shaped by migration, cultural hybridity, and social inequality, literary themes extend beyond aesthetic concerns to engage with lived social realities and communal interactions. Purpose. This study aims to examine how contemporary literary themes influence social awareness, intercultural understanding, and community dynamics within multicultural contexts. Method. The study employs a qualitative interpretative approach using textual analysis and sociocultural criticism. Selected contemporary literary works representing diverse cultural backgrounds are analyzed to identify dominant themes and their social implications within multicultural communities. Results. This study concludes that contemporary literature contributes meaningfully to social cohesion and intercultural engagement by translating textual narratives into broader social contexts. Literary works not only reflect multicultural realities but actively participate in shaping inclusive social imaginaries and communal understanding. Conclusion. This study has significant implications for instructional practices in TFL settings and for L2 lecturers in the classroom. By understanding learners’ preferences for OCF, educators can tailor their instructional approaches to meet the specific needs of their students.